1984
DOI: 10.1159/000123890
|View full text |Cite
|
Sign up to set email alerts
|

24-Hour Changes in Catecholamine Synthesis in Rat and Hamster Pineal Glands

Abstract: The purpose of this study was to examine the 24-hour variation in endogenous tyrosine hydroxylase (TH) activity and thus catecholamine (CA) synthesis in the hamster and rat pineal gland. To determine CA synthesis a time course of the accumulation of dihydroxyphenylalanine (DOPA) after DOPA decarboxylase inhibition with m-hydroxybenzylhydrazine (NSD-1015) was measured at 0, 15 and 30 min by liquid chromatography with electrochemical detection. Animals were under long photoperiods (LD 14:10; lights on at 06.00 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…In summary, it appears likely that the nighttime rise in pineal melatonin, at least in the Syrian hamster, may be de termined not only by the synthesis and release o f N E from the sympathetic neurons at this time [4], but also by the in creased sensitivity of the [l-receptors on the pinealocyte membrane. Previously, it was generally felt that the release o f N E was the primary feature determining the nocturnal rise in pineal melatonin.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In summary, it appears likely that the nighttime rise in pineal melatonin, at least in the Syrian hamster, may be de termined not only by the synthesis and release o f N E from the sympathetic neurons at this time [4], but also by the in creased sensitivity of the [l-receptors on the pinealocyte membrane. Previously, it was generally felt that the release o f N E was the primary feature determining the nocturnal rise in pineal melatonin.…”
Section: Discussionmentioning
confidence: 94%
“…However, between 02.00 and 06.00 h there is a sharp rise in pineal melatonin content with the peak usually occurring at 04.00-05.00 h. It appears then, that the night time rise in melatonin in the hamster pineal gland could be controlled by the sensitivity o f the membrane receptors to the neurotransmitter N E . Interestingly, it has been shown that catecholamine production in the postganglionic neu rons in the Syrian hamster pineal gland also increases at night, suggesting maximal release at or just prior to the time the catecholamine receptors increase their sensitivity to the neurotransmitter [3,4], Studies in rats have shown that the number o f |)-receptors on pinealocyte membrane actually increases during the dark period [17]; whether this is also true for the Syrian hamster is not known, although the pres ent findings would suggest it is.…”
Section: Discussionmentioning
confidence: 99%
“…The pivotal role of NE in the control of rat pineal metabolic activity has been supported by several experiments: 1) intraperitoneal injections of an NAergic agonist during the day stimulate MEL synthesis with a comparable amplitude to that of the endogenous nocturnal increase (see King and Steinlechner, 1985 for review); 2) SCGx abolishes the nocturnal increase in Aanat mRNA, AA-NAT activity, and MEL synthesis (Deguchi and Axelrod, 1972b;Roseboom et al, 1996;Garidou et al, 2001); 3) electrical SCG stimulation during the day provokes an increase in MEL synthesis in the pineal gland (Bowers and Zigmond, 1980); 4) exogenous NAergic stimulation of the pineal gland in organ cultures or in perifusion (Simonneaux et al, 1989) or of pinealocytes in primary culture Simonneaux et al, 1994b) induces a large increase in AA-NAT activity and MEL release; 5) the synthetic rate and renewal of NE in the pineal gland are higher at night than during the day (Brownstein and Axelrod, 1974;Craft et al, 1984); and 6) the use of pineal microdialysis to study the in situ regulation of MEL synthesis has demonstrated the positive coupling between the nighttime release of NE and stimulation of MEL synthesis (Drijfhout et al, 1993(Drijfhout et al, , 1996c.…”
Section: A Noradrenergic Regulation Of Melatonin Synthesis In the Ramentioning
confidence: 99%
“…Agonists typically downregulate (i-adrenoceptors in cell membranes [9,23]. Although the norepinephrine (NE) con tent of the hamster pineal exhibits no circadian rhythm, the catecholamine synthesis is significantly higher at night than during the day [4] and it is very likely that NE release also increases at night. The low receptor numbers at 04:00 h may therefore be explained as a downregulation of the receptors by the agonist NE.…”
mentioning
confidence: 99%